(untitled) (Research, Society and Development, 2020)
This research aimed to evaluate the effect of silicon on the physical and chemical fruit traits and the incidence of pest insects in Physalis peruviana. The experiment was carried out in a randomized block design, with three treatments: T1- control (absence of silicon); T2- Agrisil® (8 g L-1 of SiO2) and T3- ​​Insecto® (40 g L-1 of SiO2 derived from diatomaceous earth), with 14 blocks for entomological analysis and 10 blocks for the fruit traits. The silicon promoted an increase in the longitudinal (40 g L-1 of SiO2) and transverse (8 g L-1 or 40 g L-1 of SiO2) fruit with chalice diameter, and also in the transverse diameter without chalice (8 g L-1 of SiO2). On the other hand, no significant effects were found between silicon sources and the control for the longitudinal diameter without chalice and soluble solids content. For the entomofauna, there was no significant difference between treatments regarding the incidence of whitefly nymphs, green leafhopper and coleoptera (sp. 1). However, silicon (8 g L-1 or 40 g L-1 of SiO2) promoted a lower incidence of the adult stage of the whitefly, probably due to the non-preference of this stage of the insect by plants treated with silicon. Thus, it is concluded that the silicate leaf fertilization contributes to the increase of the fruit physical characteristics and reduces the incidence of whitefly adults in P. peruviana.